Impact of Inertial and External Forces on Joint Dynamics of Robotic Manipulator: Experimental Insights - Sharkawy, Abdel-Nasser (Peneliti Teknologi Teknik Indonesia, 2025)
In this paper, the effect of the inertial and external forces applied on the links of the robotic manipulator is studied and investigated on the manipulator joints’ parameters through experimental analysis. For this investigation and experiments, KUKA LWR manipulator is used and structured as a 2-DOF manipulator. Experimental work is carried out by commanding a sinusoidal joint motion to the two joints of the manipulator. Different scenarios are studied such as motion with free of collisions, motion with collision on the link between the two joints of the manipulator, motion with collision on the end-effector, and motions with different constant joint speeds. The diagrams of the position, velocity, acceleration, and torque of the manipulator joints are obtained and recorded from KUKA robot controller and then investigated and evaluated. The results reveal that during a motion free of collision, small spikes are found on the signals of the joint position, velocity, acceleration, and torques. These spikes resulted from the inertial forces applied on the joint. During a motion with collision, the signals of joint position, velocity, acceleration, and torque are highly affected due to the collision, inertial forces, and friction. During a collision on the end-effector, the torques of both joints are highly affected. During a collision on a link between the two joints, the torque of the first joint is highly affected, and the torque of the second joint is slightly affected. When the speed of the joint is increased, the torque signal is highly affected. These findings provide insights into the dynamic behavior of robotic manipulators under external forces, with implications for improving control algorithms and collision detection systems.